Prediksi Bed Occupancy Ratio (BOR) Menggunakan Metode Monte Carlo - Dendi Ferdinal; Sarjon Defit; Yuhandri Yunus (Jurnal Informasi dan Teknologi, 2021)
Planning for medical personnel, support staff and hospital facilities for the future is very important in order to carry out excellent and optimal services. Management must be able to predict the percentage of bed use based on a certain period of time or Bed Occupancy Ratio (BOR), in order to see the needs of medical personnel, supporting personnel and hospital facilities. To predict BOR in the future, a Monte Carlo simulation can be carried out using data on the day care for the Second Floor Baby care room in 2017, 2018 and 2019. The Second Floor Baby Room has a bed capacity of 12 units. The prediction rate for the treatment room using the Monte Carlo simulation is 93.09% for 2018 predictions and 89.78% for 2019. So this Monte Carlo simulation method simulation can be used in predicting BOR in hospitals. For the 2020 simulation, the BOR is 77.42% with a total treatment day of 3391.